Intonational Commitments. (25th March 2022) - Rudin, Deniz
Abstract: This paper presents an analysis of inquisitive rising declaratives (Gunlogson 2001, Jeong 2018 ) within the Table model (Farkas & Bruce 2010 ). On this account, intonational tunes are modifiers of context update functions: rising intonation removes the speaker commitment component of a context update. This delivers a compositional account of the contributions of sentence type and intonational tune to the illocutionary mood of an utterance, showing how the semantic type of declarative sentences, the rising intonational tune, and a general-purpose utterance function (Farkas & Roelofsen 2017 ) conspire to derive the basic discourse effect of rising declaratives without any construction-specific stipulations. The account makes use of only the most fundamental representational primitives independently necessary to model assertions and neutral questions, showing that rising declaratives can be accounted for without recourse to projected commitments, metalinguistic issues, or explicit marking of commitment strength, evidence source, or epistemic bias (cf. Gunlogson 2008, Northrup 2014, Malamud & Stephenson 2015, Farkas & Roelofsen 2017 ). Inferences of bias generated by rising declaratives are accounted for with a novel pragmatics for the Table model, formalizing what is implicit in discussions of the role played in the model by speaker commitments and projected Common Grounds.